Pengelolaan Lingkungan Hidup Di Kampung Naga Dalam Tinjauan Prinsip-Prinsip Etika Lingkungan - RUSMANA, Adang ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human and environment are unity whole that can not be separated from one another. Efforts to use the environment and the universe who are or made by human were intended to enhance development-oriented economic value and human welfare. Such efforts become as natural and environmental issues continue to be exploited without limit, giving rise to serious problems such as disruption of the balance of the ecosystem and the environment. Environmental management in Kampung Naga provides an overview of new and may be an alternative solution for the preservation of natural and environmental sustainability in Indonesia. This study aims to inventory a variety of information about environmental management of Kampung Naga and explain the relevance and impact on the environment and nature in Indonesia . This study is a qualitative library research of philosophy derived from literature that comes with observation. Data corresponding literature and has been classified are used as a staple. This study also uses elements methodical verstehen, analysis, interpretation and heuristics. This study resulted in an overview of environmental management in Kampung Naga is guided by pikukuh and aligned with the principles of nature of the pattern of planning, utilization, regulation and restoration. Environmental management in Kampung Naga into harmony with the four principles of environmental ethics, are containing an attitude of respect for nature, responsibility, have a sense of solidarity and simple and harmony with nature. The study also went on to become an alternative solution to the environmental conditions in Indonesia that exploited without limit.